Paradiplomasi Provinsi DKI Jakarta Terkait Penyelenggaraan Formula E - Fadhil Ramadhan; Hermini Susiatiningsih; Fendy Eko Wahyudi (Journal of International Relations, 2022)
Various kinds of international sporting events have been held in different branches and scales such as Olympics, Asian games, Football World Cup, Formula 1, Formula E and so on. Of the various kinds of international sporting events that exist, countries in the world compete with each other for positions as organizers. However, with the development of globalization, state is no longer the only actor competing to become the organizer of international sporting events. Currently, the regional government of a country is also competing to become the organizer of international sporting events, as is the case with the DKI Jakarta Provincial Government in collaboration with FEO to organize Formula E Jakarta. The foreign cooperation relationship carried out by DKI Jakarta Provincial Government and FEO in the context of organizing Formula E Jakarta itself is an example of paradiplomacy. This research aims to describe the process of paradiplomacy carried out by DKI Jakarta Provincial Government with FEO related to the implementation of Formula E using the concept of paradiplomacy and political system theory. This research uses a qualitative research approach with a descriptive type of research. The results of this research indicate that the paradiplomacy carried out by DKI Jakarta Provincial Government can be successful because of serious preparation and negotiation, as well as the common vision with FEO.